What's Happened to Italian Adolescents During the COVID-19 Pandemic? A Preliminary Study on Symptoms, Problematic Social Media Usage, and Attachment: Relationships and Differences With Pre-pandemic Peers - Muzi, Stefania; Sansò, Alessandra; Pace, Cecilia Serena (Frontiers in Psychiatry, 2021)
Italian adolescents were confined at home for three months due to the COVID-19 pandemic, which exposed them to feelings of fear, uncertainty, and loneliness that may have increased their vulnerability to emotional-behavioral symptoms (e.g., anxiety) and binge-eating attitudes. Potential risk factors for these psychopathological symptoms are problematic social media usage and attachment insecurity. Therefore, this study aimed: (1) to assess emotional-behavioral symptoms, binge eating, problematic social media usage, and attachment representations of adolescents during the pandemic, comparing them with prepandemic similar samples; (2) to investigate relationships among variables, exploring the role of problematic social media usage and insecure attachment as risk factors for more psychopathological symptoms. Participants were 62 community adolescents aged 12–17 years, enrolled through schools, and assessed online through the following measures: Youth Self-Report for emotional-behavioral problems, Binge-Eating Scale for binge eating, Social Media Disorder Scale for problematic social media usage, and the Friends and Family Interview for attachment. The main results were: 1) 9.4% of adolescents showed clinical rates of emotional-behavioral symptoms and 4.8% of binge eating attitudes. The comparison with pre-pandemic samples revealed that pandemic teenagers showed lower internalizing, but higher other problems (e.g., binge drinking, self-destructive behaviors) and more problematic social media usage than pre-pandemic peers. No differences in binge-eating attitudes and attachment were revealed (76% secure classifications). 2) Problematic social media usage was related to more binge eating and emotional-behavioral problems, predicting 5.4% of both delinquent and attention problems. Attachment disorganization predicted 16.5% of internalizing problems, somatic complaints, and social and identity-related problems. In conclusion, confinement did not increase adolescents’ internalizing symptoms -i.e. vulnerability to mood disorders of an anxious-depressive type- which even decreased. However, teenagers may have expressed their discomfort through other problems and symptoms of social media disorder. Further studies should explore the role of adolescents’ problematic social media usage and attachment insecurity as risk factors for additional psychopathological symptoms.